Re-visioning Drug Use: A Shift Away From Criminal Justice and Abstinence-based Approaches - Michelle Pelan (Social Work and Society)
This paper outlines the need for a radical re-visioning of drug use in the United States, with a particular focus on New York. It begins by describing the current landscape of both national and state drug policy and showing how these current policies inform failing practices. It demonstrates how these practices, namely incarceration and abstinence-only treatment, are exacerbating the harms of substance use for individuals, families and communities, and society and public safety, as well as how they are contributing to racism. The author then suggests harm reduction as an alternative approach, describing the ways harm reduction can improve drug treatment and outcomes. The final section offers implications for social work, specifically examining the compatibility between harm reduction and social work, as well as the opportunities for integration. The author additionally proposes recommendations at the levels of perspective, policy, and practice, citing examples in which these recommendations have demonstrated success.